ÓLEO ESSENCIAL DE Eucalyptus grandis Hill ex Maiden NO ESTÍMULO À MICORRIZAÇÃO DE MUDAS DE SIBIPIRUNA (Caesalpinia peltophoroides Benth.) - Ricardo Bemfica Steffen; Zaida Inês Antoniolli; Gerusa Pauli Kist Steffen; Rodrigo Ferreira da Silva (Ciência Florestal, 2012)
The secondary metabolites extracted from forest species forming ectomycorrhizal could stimulate the symbiosis between ectomycorrhizal fungi and natives forest species of Rio Grande do Sul state. The aim of this work was to evaluate ectomycorrhizal association and the seedlings growth of inoculated and non-inoculated Sibipiruna with Pisolithus microcarpus (Cooke & Massee) ectomycorrhizal fungus and submitted and not submitted to the application of the essential oil of Eucalyptus grandis, in greenhouse conditions. The essential oil was solubilized and applied with manual spray during periods of 0, 7 and 14 days from the date of seedlings transplanting. A randomized design with seven repetitions was used. After 90 days of plant growth, it was evaluated the seedling colonization degree, the height, the stem diameter, the root length and the dry mass of shoots. The eucalyptus essential oil stimulates the occurrence of ectomycorrhizal on Sibipiruna seedlings, thus providing high seedling development when inoculated with Pisolithus microcarpus.